Exchange rate volatility in Nigeria: Consistency, persistency & severity analyses - Babatunde W. Adeoye; Akinwande A. Atanda (CBN Journal of Applied Statistics, 2011)
The adoption of the International Monetary Fund (IMF) Structural Adjustment Programme (SAP) in 1986 resulted in the transition from fixed exchange rate regime to floating exchange rate regime in Nigeria. Ever since, the exchange rate of naira vis-à-vis the U.S dollar has attained varying rates all through different time horizons. On this basis, this study examines the consistency, persistency, and severity (degree) of volatility in exchange rate of Nigerian currency (naira) vis-a-vis the United State dollar using monthly time series data from 1986 to 2008. The standard Purchasing Power Parity (PPP) model was used to analyze the long-run consistency of the naira exchange rate while the time series properties of the data was examined using the ADF and PP approach, the stationary process, and order of the incorporated series. The ARCH and GARCH models were used to examine the degree or severity of volatility based on the first difference, standard deviation and coefficient of deviation estimated volatility series for the nominal and real exchange rate of naira vis-a-vis the U.S dollar. The result indicated the presence of overshooting volatility shocks. The econometric analyses further revealed that the nominal and real exchange rates of naira vis-a-viz the U.S dollar are not with the traditional longrun PPP model. All the incorporated measures of volatility indicated presence and persistency of volatility in the nominal and real exchange rate for naira vis-à-vis U.S dollar in Nigeria. This however proves the ineffectiveness of monetary policy in stabilizing exchange rate and therefore, calls for the need of more tightened measures especially in controlling the high demand for foreign currency.
Keywords: C10; E3; F31.; 330; Exchange rate; volatility; Purchasing Power Parity (PPP); Consistency; Persistency; Severity/ Degree; ARCH; GARCH